2021
DOI: 10.3390/su13094627
|View full text |Cite
|
Sign up to set email alerts
|

A C-Vine Copula-Based Quantile Regression Method for Streamflow Forecasting in Xiangxi River Basin, China

Abstract: In this study, a C-vine copula-based quantile regression (CVQR) model is proposed for forecasting monthly streamflow. The CVQR model integrates techniques for vine copulas and quantile regression into a framework that can effectively establish relationships between the multidimensional response-independent variables as well as capture the upper tail or asymmetric dependence (i.e., upper extreme values). The CVQR model is applied to the Xiangxi River basin that is located in the Three Gorges Reservoir area in C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 66 publications
(69 reference statements)
0
5
0
Order By: Relevance
“…The drawable vine (D-vine) and canonical vine (C-vine) are two common structures of vines (Li et al 2021). It is necessary to mention that the tree sequence of the vine copula in The main difference between C-and D-vine copulas is their tree sequence and the choice of roots and nodes in dimensions more than 3.…”
Section: C-and D-vine Structurementioning
confidence: 99%
See 1 more Smart Citation
“…The drawable vine (D-vine) and canonical vine (C-vine) are two common structures of vines (Li et al 2021). It is necessary to mention that the tree sequence of the vine copula in The main difference between C-and D-vine copulas is their tree sequence and the choice of roots and nodes in dimensions more than 3.…”
Section: C-and D-vine Structurementioning
confidence: 99%
“…It is necessary to mention that the tree sequence of the vine copula in The main difference between C-and D-vine copulas is their tree sequence and the choice of roots and nodes in dimensions more than 3. The C-vine copula has a star shape in the tree sequence, while the D-vine copula has a straight structure (Li et al 2021). Similarly, in the tree T2, in the C-vine copula (Figure 3, Left), e = 2,3|1 is edge, 1,3 and 1,2 call the node and root, respectively and for D-vine copula (Figure 3, Right), e = 3,2|1 is edge, 3,1 and 1,2 call the node…”
Section: C-and D-vine Structurementioning
confidence: 99%
“…From the many studies that were performed in previous years, it is now known that flow and watershed characteristics should be log-transformed to form a near-linear relationship. Many studies have also previously shown the application of the Ordinary Least Squares technique for estimating streamflow by employing stream gauging stations [11][12][13]. However, grouping the stations according to their watershed and meteorological characteristics and then engaging them in a regression analysis, whether linear or non-linear, is a concept yet to be fully explored in different climatic regions of the world.…”
Section: Regression Analysismentioning
confidence: 99%
“…The application of many global and regional climate models in CORDEX has helped to characterize the strength and the weaknesses of several regional climate models in terms of their climate projection capabilities for the selected basins [10,11]. Regression approaches in ungauged regions often rely on empirical data, despite not offering an understanding of the watershed hydrology and characteristics, but their data-driven methodology helps obtain useful correlations between the precipitation and streamflow without the need of intense variable availability that is required for physical models [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Copula theory, which has been rapidly developed in hydrological and geotechnical engineering in recent years, provides an effective way to solve the parameter correlation problem [11][12][13][14]. The basic content of Copula theory can be summarized as follows: identify the marginal distribution of each variable as well as pick a copula function to link the marginal distribution functions together.…”
Section: Introductionmentioning
confidence: 99%